HUMAN COMPUTER INTERACTION DESIGN ENHANCING USABILITY IN MOBILE COMPUTING APPLICATIONS - Filbert Ivander; Erlanie Sufarnap; Afen Prana Utama = Sembiring (Journal of Computer Science Advancements, 2026)
The rapid growth of mobile computing applications has intensified the need for effective Human Computer Interaction design to ensure high usability and positive user experience. Mobile applications are used in diverse contexts characterized by limited screen space, touch-based interaction, and frequent interruptions, making usability a critical determinant of system acceptance and sustained use. This study aims to examine how Human Computer Interaction design principles contribute to enhancing usability in mobile computing applications. The research employed a mixed-methods approach combining usability testing, standardized usability questionnaires, and qualitative user interviews to capture both performance-based and perceptual usability outcomes. Quantitative data focused on task completion time, error rates, task success, and perceived usability, while qualitative data explored user interaction experiences and design-related challenges. The results indicate that mobile applications designed with clear navigation structures, consistent visual elements, and effective feedback mechanisms demonstrate significantly higher usability scores, faster task completion, and lower error frequency. Qualitative findings further reveal increased user confidence, reduced cognitive load, and higher satisfaction when interacting with well-designed interfaces. The study concludes that Human Computer Interaction design plays a central role in enhancing usability in mobile computing applications. Systematic integration of user-centered design principles throughout the development process is essential for creating efficient, effective, and satisfying mobile applications across various domains.